Evaluation of Occupational Safety, Health, and Environmental Aspects in the Use of Geofoam on Clay Shale Soil as an Alternative Embankment Material - Suluh Damar Harbian; Agus Triyono (Eduvest - Journal of Universal Studies, 2025)
In the Cisumdawu Toll Road Construction Package 5A, at the STA 40+125–STA 40+225 area, soil material cannot be used for embankment work because the existing soil condition is clay shale. This study aims to evaluate EPS geofoam material as a substitute for soil material because it is lighter and safer from the aspects of occupational safety, occupational health, and the environment. This study uses a qualitative research design with a descriptive method, with data collected from 13 informants ranging from staff-level employees to management among the work implementers. The data were obtained through interviews with informants and observations conducted both in the field and via related documents. The data analysis techniques applied include data collection, data reduction, data presentation, and conclusion drawing with verification. The results of this study show that unstable clay shale soil, which is not strong enough to withstand the embankment load, causes cracks and landslides; HSE risk management for handling cracks and landslides in the Cisumdawu Project Package 5A has not yet been implemented; the use of EPS geofoam can minimize the potential for work accidents, reduce the risk of occupational diseases, and lower the potential for environmental pollution. Researchers recommend using EPS geofoam because it fulfills occupational safety, occupational health, and environmental requirements.